Academic Workplace Inclusivity Through the Prism of Microvalidations Among Male LGBTQIA+ Faculty Members - Salazar, Edgardo (Journal of Interdisciplinary Perspectives, 2024)
This research explored the lived experiences of male LGBTQIA+ faculty members at a local university in Cabuyao City, Laguna. It focused on understanding how inclusivity in the academic workplace, viewed through microvalidations, impacts these individuals. The study employed a qualitative research design with a phenomenological approach. Ten male LGBTQIA+ faculty members were interviewed to gather data on their experiences. Interpretative Phenomenological Analysis was used to analyze the data, resulting in thirty superordinate themes. The analysis revealed the following themes: Inclusive Environment; Restrictive Environment; Establishing Respectful Treatment and Boundaries; Discrimination Concerns; Interaction and Perception; Self-Expression Struggles; Acceptance through Positive Actions and Interactions; Colleagues as Source of Motivation and Appreciation; Students as Source of Motivation and Appreciation; Diversity, Equity, Inclusion, and Belonging; Personal Enhancements; Culture of Appreciation and Understanding; Professionalism; Personal Coping Mechanisms; Interpersonal Dynamics; Boosting One’s Confidence; Fostering One’s Authenticity; Valuing One’s Worth; Improving One’s Capability; Professional Growth and Confidence; Professional Performance; Positive Work Environment; Emotional Well-being; Job Potential Attainment; Job Satisfaction Fulfillment; Job Performance Improvement; Need for Clear Rules and Guidelines; Inclusive Facility Accommodation; Importance of Gender and Development Functions; Need for Full Acceptance. The study highlighted the crucial role of micro validations in promoting inclusivity and empowerment among male LGBTQIA+ faculty members. Affirmations significantly enhanced confidence, performance, and well-being in academic workplaces. The research emphasized the need to reassess existing norms to create fair and empowering environments for all. It called for fostering spaces where individuals feel valued, respected, and able to thrive professionally.